Influence of functionalized halloysite clays (HNT) on selected properties of multiblock (e)PBS-EG copolymer obtained by enzymatic catalysis - Gradzik, Boguslawa; Stenzel, Alexander; Boccaccini, Aldo R.; El Fray, Miroslawa (Designed Monomers and Polymers, 2015)
In this paper, we discuss the functionalization of halloysite aluminosilicate clays (HNT) with anionic surfactant - sodium dodecanoate (NaL) and their use in new polymeric nanocomposites preparation via solvent casting. The selected polymer matrix were segmented; copoly(ester-ether)s - poly(butylene succinate-co-ethylene glycol) (PBS-EG) were synthesized for the first time with the use of enzymatic catalyst from Candida antarctica lipase B. The influence of variable concentration of NaL, temperature, and time on functionalization and finally on the chemical structure (IR) and colloidal stability (zeta potential) of functionalized HNT (f-HNT) was examined. Nanocomposites were prepared via solvent casting process, where 1 wt% of HNTs and 1 wt% of f-HNT clays were added to the (e)PBS-EG solution in chloroform. The chemical structure, topography, and hydrophilic/hydrophobic properties of prepared nanocomposites were determined by nuclear magnetic resonance (1H NMR), infrared spectroscopy (IR), scanning electron microscopy, and water contact angle. It was observed that higher concentration of NaL, longer modification time, and higher temperature lead to even distribution of f-HNT into (e)PBS-EG matrix. Halloysite clays in general improved the hydrophilicity of (e)PBS-EG and f-HNT was found to act as nucleating agent during polymer crystallization.
Keywords: aluminosilicates; enzymatic synthesis; halloysite clays; nanocomposites; poly(butylene succinate) (PBS)

Porous piezoelectric ceramics with 3-3-connectivity fabricated by impregnation of cellulose paper structures - Eichhorn, Franziska; Stenzel, Alexander; Weisenseel, Bastian; Travitzky, Nahum; Kakimoto, Ken-Ichi; Greil, Peter; Fey, Tobias (Materials Letters, 2017)
Keywords: Paper derived ceramic; Piezoelectric properties; Cellulose fiber paper; Hydrophones; Porous piezoceramic